2020
DOI: 10.3389/fmicb.2020.00024
|View full text |Cite
|
Sign up to set email alerts
|

The E3 Ubiquitin Ligase SIAH1 Targets MyD88 for Proteasomal Degradation During Dengue Virus Infection

Abstract: The dengue virus presents a serious threat to human health globally and can cause severe, even life-threatening, illness. Dengue virus (DENV) is endemic on all continents except Antarctica, and it is estimated that more than 100 million people are infected each year. Herein, we further mine the data from a previously described screen for microRNAs (miRNAs) that block flavivirus replication. We use miR-424, a member of the miR-15/16 family, as a tool to further dissect the role of host cell proteins during DENV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 62 publications
(78 reference statements)
2
13
0
Order By: Relevance
“…The transient knockdown of SIAH1 reconstitutes high-level IFN response and decreases DENV replication. However, CRISPR-mediated knockout of MyD88 abrogates anti-DENV IFN response and results in an increase in DENV replication [ 219 ].…”
Section: Crispr–cas Systems For Modulating Antiviral Responsesmentioning
confidence: 99%
“…The transient knockdown of SIAH1 reconstitutes high-level IFN response and decreases DENV replication. However, CRISPR-mediated knockout of MyD88 abrogates anti-DENV IFN response and results in an increase in DENV replication [ 219 ].…”
Section: Crispr–cas Systems For Modulating Antiviral Responsesmentioning
confidence: 99%
“…Another study found that miR-424 inhibits expression of E3 ubiquitin ligase SIAH1 by activating unfolded protein response (UPR) during the infection of HeLa cells by DENV-2 ( Murphy Schafer et al, 2020 ). The downregulation of SIAH1 can inhibit the replication of DENV, which indicates that this target plays a role in the antiviral activity of miR-424, at least to a certain extent ( Murphy Schafer et al, 2020 ). SIAH1 binds to MyD88, an important transducing protein in the TLR signaling pathway, and ubiquitinates it.…”
Section: The Role Of Mirna In Regulating Denv and Related Signaling Pathwaysmentioning
confidence: 99%
“…SIAH1 binds to MyD88, an important transducing protein in the TLR signaling pathway, and ubiquitinates it. Moreover, the antiviral effect of SIAH1 is reduced in cells from which MyD88 has been deleted by CRISPR/Cas9 gene editing ( Murphy Schafer et al, 2020 ). In addition, in cells in which SIAH1 has been downregulated by miR-424 or siRNA knockout by SIAH1, the MyD88-mediated NF-kB signaling pathway is enhanced by DENV-2 infection or by imiquimod, a TLR7 ligand ( Murphy Schafer et al, 2020 ; Figure 2 ).…”
Section: The Role Of Mirna In Regulating Denv and Related Signaling Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“… Carvalho et al (2014) showed that higher NS1 levels in serum may induce a reduced TLR4 response to LPS. Recently, Murphy Schafer et al (2020) introduced an additional mechanism of TLR signaling disruption by DENV-2. DENV-2 infection induces SIAH1 expression, resulting in SIAH1 binding and ubiquitination of MyD88, an adaptor protein of TLR signaling, thereby dampening the host innate immune response and promoting viral replication.…”
Section: Inhibition Of Innate Immune Response By Denvmentioning
confidence: 99%